Smart city management from the perspective of inhabitants as the creative consumers of urban space - Gwiaździński, Emilian; Kalińska-Kula, Magdalena; Moreira Pinto, Luís (Creativity Studies, 2024)
The purpose of this article is to assess the perception of the idea of about the smart city management by its creative inhabitants. In operationalising the adopted objective, the focus is on the perception of the advantages and disadvantages of the implementation of Internet of things technologies and devices in urban space, based on the residents’ convictions and attitudes. The study was conducted using an online survey technique. The most important advantages related to the implementation of Internet of things solutions in the field of smart cities are improved convenience in everyday life (easier access to public services), optimised allocation of urban resources, creating the image of the city as a modern city and economic benefits. On the other hand, the most important disadvantages are unethical use of personal data by public administration representatives, excessive surveillance of residents, increased costs of purchasing public services, loss of control over devices/systems, and increased feeling of insecurity among residents. The variable that differentiates to some extent the advantages and disadvantages perceived by inhabitants is their age.